Analyzing the Mental Health of Students in Dealing with the Coronavirus Disease Pandemic (Covid-19) - Chamdani, Muhamad; Mahmudah, Umi; Fatimah, Siti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
This study aims to analyze mental health and anxiety levels during the COVID-19 pandemic. This study focused on students who were forced to study at home by e-learning. This study used as many as 210 students from junior high school, senior high school, and university levels which were selected randomly. Then, this study used a mixed-method by combining quantitative and qualitative approaches. Multivariate analysis of variance (MANOVA) was used to obtain empirical results to compare mental health and anxiety levels based on student age groups. The analysis results revealed there was a positive and significant influence of the students’ age group on mental health and anxiety levels during the outbreak of COVID-19. The analysis also concluded that students in the 12-15 years’ age group had the worst mental health level. Meanwhile, students in the 20-25 years’ age group are known to have the lowest anxiety level. Overall, this study found that Indonesian students experienced a decline in mental health and detected an increase in anxiety levels. The level of mental health and student anxiety has implications for their learning at home, which can lead to unsatisfactory learning outcomes.